From the Editor: On Women’s Health, progress and challenges - Pacheco-Romero, José (2019)
An important review on breast cancer treatment, artificial intelligence in human reproduction techniques, use of surgical mesh products for the transvaginal repair of pelvic organ prolapse, abrupt hormonal changes with bilateral salpingo-oophorectomy in women before age 50, association of high risk HPV infection with cardiovascular disease, meager results with treatments to prevent osteoporosis and other consequences of estrogen deprivation, are some of the Editor´s choice considered in this section on women’s health.